Per un nuovo campo disciplinare: l’interlinguistica - Vincenzo Orioles (Atti del Sodalizio Glottologico Milanese, 2017)
Interlinguistics is a field of study which investigates various phenomena relating to the encounters between two or more languages or varieties and their speakers both in the past and the present. The aim of this work is to focus the attention to the various terms at disposal, in the course of time, to describe this phenomenon: Sprachmischung (i.e. linguistic mixture) borrowing, language contact; interference and finally interlinguistics are considered. Regarding the latter label, the different definitions adopted in literature are also presented and discussed, with a preference for Roberto Gusmani’s interpretation.